La costruzione retorica del catalanismo nella storiografia contemporanea spagnola - de Lara Vázquez, Juan M. (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
The aim of this article is to examine the formation and rhetorical construction of Catalan nationalism in contemporary historiography. At the beginning of the 19th century, a new historiographical tendency appeared that tended to revise the unitary Spanish history by providing new interpretations that saw and justified the creation of a regional identity separate from the rest of the current Spanish state. We will therefore study the emergence of the main historians who promoted this new trend throughout the last century, concentrating on the main controversial historical events that have been most debated. Finally, the effects and state of these academic historiographical debates today will be examined. Spain; Catalonia; History; Invention; Nation; Catalanism.